Dietary habits in elite soccer players - Petri, C.; Mascherini, G.; Pengue, L.; Galanti, G. (Sport Sciences for Health, 2016)
Purpose: Physical training involves a balance among dietary intake, energy used and increasing physical activity. The keys to improve performance are diet and nutritional assessments. Accordingly, the purpose of this study is to assess dietary habits in a team of soccer players. Methods: This study includes 28 elite soccer players (aged 27.88 ± 4.55 years, height 1.84 ± 0.06 m). Dietary habits, bio impedance analysis and skinfold thickness were examined throughout the soccer season of 2014-2015. Results: Body composition was found to be in the normal range. A significant decrease in fat-free mass occurred in the end-season (T2, 72.8 ± 5.2; T3, 71.7 ± 5.6; p = 0.001). These results show dietary habits which are not in accordance with the recommended international guidelines. Conclusions: Results suggest that development of a nutrition programme would be helpful to maintain health and to improve performance. ABSTRACT FROM AUTHOR